Deoxyribonucleic Acid as a Tool for Digital Information Storage: An Overview - Patel, Ashish; Joshi, CG (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Current data storage technologies cannot keep pace longer with exponentially growing amounts of data through the extensive use ofsocial networking photos and media, etc. The "digital world” with 4.4 zettabytes in 2013 has predicted it to reach 44 zettabytes by 2020.From the past 30 years, scientists and researchers have been trying to develop a robust way of storing data on a medium which is denseand ever-lasting and found DNA as the most promising storage medium. Unlike existing storage devices, DNA requires no maintenance,except the need to store at a cool and dark place. DNA has a small size with high density; just 1 gram of dry DNA can store about 455exabytes of data. DNA stores the informations using four bases, viz., A, T, G, and C, while CDs, hard disks and other devices stores theinformation using 0’s and 1’s on the spiral tracks. In the DNA based storage, after binarization of digital file into the binary codes, encodingand decoding are important steps in DNA based storage system. Once the digital file is encoded, the next step is to synthesize arbitrarysingle-strand DNA sequences and that can be stored in the deep freeze until use. When there is a need for information to be recovered,it can be done using DNA sequencing. New generation sequencing (NGS) capable of producing sequences with very high throughputat a much lower cost about less than 0.1 USD for one MB of data than the first sequencing technologies. Post-sequencing processingincludes alignment of all reads using multiple sequence alignment (MSA) algorithms to obtain different consensus sequences. Theconsensus sequence is decoded as the reversal of the encoding process. Most prior DNA data storage efforts sequenced and decodedthe entire amount of stored digital information with no random access, but nowadays it has become possible to extract selective files(e.g., retrieving only required image from a collection) from a DNA pool using PCR-based random access. Various scientists successfullystored up to 110 zettabytes data in one gram of DNA. In the future, with an efficient encoding, error corrections, cheaper DNA synthesis,and sequencing, DNA based storage will become a practical solution for storage of exponentially growing digital data.
Keywords: Byte; Decoding; Digital information; Encoding; PCR; Sequencing